Pengaruh Promosi, Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Konsumen pada Cafe Iconix Grill end Suki Padang - Belviyanto, Ridho; Haryati, Rice; Sunreni, Sunreni (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
This research aims to determine which indicators are dominant in terms of promotion, service quality, product quality, and consumer satisfaction at Cafe Iconix Grill End Suki Padang as well as the influence of promotion, service quality, and product quality on consumer satisfaction at Cafe Iconix Grill End Suki Padang partially and simultaneously. This study uses a quantitative approach. The research sample was 98 respondents. Data collection uses a valid and reliable questionnaire. Data analysis was carried out using multiple linear regression analysis, testing hypotheses t and F. Research results The dominant indicator of promotion is advertising, the dominant indicator of service quality is reliability, the dominant indicator of product quality is special characteristics and the dominant indicator of consumer satisfaction is repurchase. The promotion has a positive and insignificant effect on consumer satisfaction, service quality has a positive and insignificant effect on consumer satisfaction, product quality has a positive and significant effect on consumer satisfaction, and Promotion, service quality, and product quality simultaneously have a positive and significant effect on consumer satisfaction at Cafe Iconix Grill End Suki Padang.